KERJASAMA BADAN NASIONAL PENANGGULANGAN BENCANA (BNPB) DENGAN ASEAN COORDINATING CENTER FOR HUMANITARIAN ASSISTANCE (AHA CENTER) DALAM BIDANG MITIGASI BENCANA DI INDONESIA PADA PERIODE 2016 - 2020 - Kevin Abdillah, (2023)
This study aims to analyze the collaboration between the National Disaster Management Agency (BNPB) and the Asean Coordinating Center for Humanitarian Assistance (AHA CENTER) in the field of disaster mitigation in Indonesia in 2016-2020. This study uses a qualitative approach with secondary data collection techniques. The data source for this research refers to BNPB annual reports from 2016 to 2020 and annual report AHA Center. The results of this study indicate that the collaboration between BNPB and the AHA Center can improve Indonesia's mitigation capabilities. This refers to the decline in Indonesia's disaster risk index (IRBI) from 150.58 in 2016 and fell to 141.65 in 2020. The collaboration includes training for ASEAN ERAT members, study visit, donations for disaster victims, Infrastructure Improvements, and so on. Challenges during the period of cooperation between the two organizations included: competence of volunteers and officers, awareness of disasters by the community, and social vulnerability. Nonetheless, the collaboration between BNPB and the AHA Center can have a positive impact on the progress of Indonesia's mitigation capabilities.